2015
DOI: 10.1007/s00411-015-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling radiation-induced cell death: role of different levels of DNA damage clustering

Abstract: Some open questions on the mechanisms underlying radiation-induced cell death were addressed by a biophysical model, focusing on DNA damage clustering and its consequences. DNA "cluster lesions" (CLs) were assumed to produce independent chromosome fragments that, if created within a micrometer-scale threshold distance (d), can lead to chromosome aberrations following mis-rejoining; in turn, certain aberrations (dicentrics, rings and large deletions) were assumed to lead to clonogenic cell death. The CL yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 75 publications
4
27
0
Order By: Relevance
“…Clustered DNA damage with dense IRIF along the particle track can dramatically increase the probability of chromosomal aberrations compared to X-rays in human lymphocytes [59] and their hematopoietic progenitors [60]. Extreme proximity of DSBs in clustered lesions may also give rise to increased chromosomal rearrangements [61] which was in agreement with computational modeling data [62]. Utilizing cytogenetic techniques like G2 premature chromosome condensation (G2 PCC) and multicolor banding fluorescence in situ hybridization (mFISH), it has been shown that charged particle radiation is more effective at inducing chromosomal aberrations when compared to low LET radiation [63,64,65,66].…”
Section: Complex Dna Damage and Repairsupporting
confidence: 59%
“…Clustered DNA damage with dense IRIF along the particle track can dramatically increase the probability of chromosomal aberrations compared to X-rays in human lymphocytes [59] and their hematopoietic progenitors [60]. Extreme proximity of DSBs in clustered lesions may also give rise to increased chromosomal rearrangements [61] which was in agreement with computational modeling data [62]. Utilizing cytogenetic techniques like G2 premature chromosome condensation (G2 PCC) and multicolor banding fluorescence in situ hybridization (mFISH), it has been shown that charged particle radiation is more effective at inducing chromosomal aberrations when compared to low LET radiation [63,64,65,66].…”
Section: Complex Dna Damage and Repairsupporting
confidence: 59%
“…In previous works [e.g., Ref. ( 13 )], where the threshold distance d was considered as an adjustable parameter, a d value of 5 μm led to good agreement with experimental survival curves for AG1522 human fibroblasts and V79 hamster fibroblasts exposed to different radiation qualities. However, this value seems to be larger than most estimations available in the literature.…”
Section: Methodssupporting
confidence: 62%
“…Therefore, we chose not to provide a definition for the quantity “CL,” leaving the mean number of CLs per unit radiation dose and per unit DNA mass (that is, the mean number of CLs per Gy and per Dalton, which can be easily converted into CLs per Gy and per cell) as an adjustable parameter. In a previous work ( 13 ), CL yields for different radiation qualities showed good agreement with yields of kilo-base-pair (kbp) DNA fragments, suggesting that DSB clusters at the kbp scale, possibly in addition to other levels of clustering, may play a relevant role.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…DNA complex damage is critical for the cell because it can lead to important biological consequences such as chromosome aberrations, cell death, and cell conversion to malignancy [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%